Impact of additives in Jet-A fuel blends on combustion, emission and exergetic analysis using a micro-gas turbine engine. (15th September 2020) - Manigandan, S.; Atabani, A.E.; Ponnusamy, Vinoth Kumar; Gunasekar, P.
Graphical abstract: Abstract: This study focuses on combustion, emission, and performance analysis of JET-A fuel blends with various additives using a micro gas turbine engine. The amount of oxygen in fuel blends and atomization are the crucial parameters in the production of a higher combustion rate with less emission. Therefore, various ratios of additives (ethanol and pentanol) are blended with biofuel (rapeseed and canola-sunflower oil) to form the JET-A fuel blends by using Kay's and Grunberg-Nissan mixing rules. The combustion, performance and emission parameters under different engine loads were examined. Results showed that all the blends logged higher static thrust with an appreciable reduction rate in the consumption of the fuel. Among different fuel blends, R20E (Jet-A 70% fuel, 20% Rapeseed, and 10% ethanol) showed 35% increase in static thrust associated with 41% reduction in thrust specific fuel consumption. Moreover, the blends R20E and CS20E (Jet-A fuel 70%, Canola- Sunflower 20% and 10% ethanol) indicated 24% and 10% increase in thermal efficiency respectively due to the influence of ethanol concentration and higher oxygen content. In addition, these fuel blends generate less emission of environmental unfriendly harmful gases, including NOx, CO, and HC, compared to neat Jet-A fuel. Results revealed that the exergy destruction values are higher for the combustion chamber than the other conventional fuel components.